P170 Digital life, digital death – an App to fill the gap. (1st October 2013) - Taylor, Ros; Moore, Victoria; McLaughlin, Kimberley; Russell, Sarah
Abstract : Context: The crisis of illness provokes people to review their life, dwell on regrets and unfinished business, think about bucket lists and maybe their funeral. This critical time however is dominated by treatment, panic and anxiety, and these important tasks are often neglected and delayed. Lawyer, Victoria Moore and business partner Morag Cormack have designed a simple, elegant iPhone App to digitally capture life's special moments, in the midst of life, long before an illness takes hold. Victoria was inspired to create the Legacy Organiser App after completing her will – she felt there was so much more to record than simply 'who gets what'! The Legacy Organiser App allows you to: Save photos for your 'life album' Choose music to create the 'soundtrack of your life' Create a 'bucket list' Record your life lessons, your biggest regret, your best kiss! The 'farewell and will' section lets you record funeral wishes Palliative Potential: This innovative app provides opportunities for those in the palliative phase to: Use as a therapeutic digital tool to provoke new conversations 'Tell me about that regret', 'talk me through your bucket list' 'Have you thought about how you might celebrate your life?' Use as an advance care planning platform to capture wishes, not simply about funerals but about preferences for future care. Create a generativity document (Chochinov Dignity Therapy) Carry choices around with them - mobile phones allow instant access and sharing of key preferences with others Next steps: Therapeutic pilot with 10 patients download App to patients iPhone demonstrate potential homework to complete a section eg bucket list review together at next clinic. First impressions – patients love it, provoking different conversations! Evaluation questionnaire currently in design. Co-create new sections to support advance care planning eg care preferences, with App inventor Victoria Moore